2013
DOI: 10.1038/nchembio.1408
|View full text |Cite
|
Sign up to set email alerts
|

Protonation drives the conformational switch in the multidrug transporter LmrP

Abstract: Multidrug antiporters of the Major Facilitator Superfamily couple proton translocation to the extrusion of cytotoxic molecules. The conformational changes that underlie the transport cycle and the structural basis of coupling of these transporters have not been elucidated. Here we utilized extensive Double Electron Electron Resonance measurements to uncover the conformational equilibrium of LmrP, a multidrug transporter from L. lactis, and to investigate how protons and ligands shift this equilibrium to enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 58 publications
9
101
1
Order By: Relevance
“…This methodology has been successfully applied to define coupled conformational cycles for a number of transporter classes (13,(26)(27)(28)(29)(30)(31)(32). We find that patterns of distance distributions between pairs of spin labels monitoring the intra-and extracellular sides of Mhp1 are consistent with isomerization between the crystallographic inward-and outward-facing conformations.…”
mentioning
confidence: 70%
“…This methodology has been successfully applied to define coupled conformational cycles for a number of transporter classes (13,(26)(27)(28)(29)(30)(31)(32). We find that patterns of distance distributions between pairs of spin labels monitoring the intra-and extracellular sides of Mhp1 are consistent with isomerization between the crystallographic inward-and outward-facing conformations.…”
mentioning
confidence: 70%
“…Protonation has been shown to induce conformational changes in other protoncoupled MFS transporters. For example, in FucP, protonation of a key carboxyl was suggested to facilitate the transition from extracellular-to cytoplasm-facing (45,46); in EmrD, decreasing the pH led to opening of the cytoplasmic cleft (47); in LacY, deprotonation enabled a conformational change of the empty transporter (10,48,49); and a recent study suggested a protonation event as a molecular switch between conformations in LmrP (50). Given that mutating D33 to Asn resulted in a very similar behavior to that of the gating mutants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In two other well characterized but more distant MFS multidrug antiporters from Gram-positive bacteria, LmrP and QacA, membrane-embedded carboxylic acids in various TMs have been shown to play a role in substrate binding and proton translocation, although the location of the carboxylic amino acids is not conserved (62)(63)(64)(65)(66). Among the well characterized MFS antiporters, the highest similarity and, presumably, mechanism is indeed observed between BbMAT and rVMAT2 (Fig.…”
Section: H]mppmentioning
confidence: 96%